2019
DOI: 10.1128/msphere.00416-19
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus Mismatch Repair MSH2 Homolog Is Important for Virulence and Azole Resistance

Abstract: The genetic stability of every living organism depends on accurate DNA replication and repair systems. Here, we investigated the Aspergillus fumigatus MSH2 mismatch repair (MMR) gene MshA and how it impacts virulence and the evolution of azole resistance. We examined mshA gene variation in 62 environmental and clinical A. fumigatus strains. We have observed 12 strains with variants (18.2%), and 8 strains among them showed missense variants. We demonstrated that A. fumigatus mshA null mutants are haploid and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…New studies implicating various cellular components and pathways involved in azole resistance resulted in significant advances on the topic of azole resistance in A . fumigatus [ 148 , 149 , 150 , 151 ].…”
Section: Mechanisms Of Antifungal Resistancementioning
confidence: 99%
“…New studies implicating various cellular components and pathways involved in azole resistance resulted in significant advances on the topic of azole resistance in A . fumigatus [ 148 , 149 , 150 , 151 ].…”
Section: Mechanisms Of Antifungal Resistancementioning
confidence: 99%
“…They showed that exposing Aspergillus flavus to azoles changed the sensitivity of the fungus to the antifungals itraconazole, voriconazole, and posaconazole, evidencing the development of resistant phenotypes, and constituting the first case report of antifungal resistance induced by azole exposure. Dos Reis et al [101] investigated the Aspergillus fumigatus MSH2 mismatch repair (MMR) gene mshA and its impact on virulence and evolution of azole resistance [101]. The mshA mutant A. fumigatus strain showed significantly reduced virulence in a neutropenic murine model of invasive pulmonary aspergillosis.…”
Section: Azole Resistance Of Aspergillus: Implications In Clinic and mentioning
confidence: 99%
“…These compensatory mechanisms orchestrate a rapid and appropriate response to stress, allowing the cell to "buy time" to acquire mutations in critical genes and/or undertake gross chromosomal changes, consequently leading to permanent resistance [31,32]. The acquisition of such mutations in genes associated with resistance may occur in the presence of specific mutations/absence of DNA repair mechanisms, such as mismatch repair (MSH2), resulting in increased antifungal tolerance and virulence [32,33]. Of note, the link between MSH2, in vitro tolerance, and clinical tolerance is uncertain [34,35].…”
Section: Antifungal Tolerance Molecular Mechanisms and Its Implicatiomentioning
confidence: 99%